Cost-Effectiveness Analysis of Olaparib Maintenance Treatment for Germline BRCA-Mutated Metastatic Pancreatic Cancer - Li, Na; Zheng, Huanrui; Huang, Yanlei; Zheng, Bin; Cai, Hongfu; Liu, Maobai (Frontiers in Pharmacology, 2021)
Background: The PARP inhibitor olaparib has been shown to have clinical efficacy in patients with a germline BRCA mutation and ovarian or breast cancer. However, the high treatment cost associated with this drug limits its viability as a clinical treatment option. This work aims to evaluate the cost-effectiveness of olaparib as a maintenance treatment for metastatic pancreatic cancer from the perspective of the US and China healthcare systems and provides valuable suggestions for clinical decision making. Method: A three-state Markov model(progression-free, progressed disease, death) was constructed using TreeAge Pro 2015 software to evaluate the economic value of olaparib versus placebo maintenance treatment for metastatic pancreatic cancer based on the clinical data derived from phase III randomized controlled trial (POLO, ClinicalTrials.gov number, NCT02184195). Total costs, quality-adjusted life years (QALYs) and incremental cost-effectiveness ratio (ICER) were used as economic indicators for this analysis. A 5-years horizon and 5%/year discount rates were used. One-way sensitivity analysis and probabilistic sensitivity analysis(PSA) were performed to assess the model uncertainty. Results: The incremental cost-effectiveness ratios (ICERs) of the use of olaparib versus placebo in China and the US were 6694/QALY and 13327/QALY, respectively. All ICERs were far below the thresholds of 30829 in China and 50000 in the US. Sensitivity analysis confirmed a stable economic advantage in the use of olaparib versus placebo as maintenance therapy in China and the US. Conclusion: Olaparib was estimated to be more cost effective than placebo for the maintenance therapy of patients with a germline BRCA mutation and pancreatic cancer in China and the US at thresholds of 30829 and 50000 per QALY, respectively.